Credit Risk Management in Banking Institutions: Comparison between Chinese Banks and UK Banks - YU, LIN (2009)
The recent international financial market turmoil has a great effect on the banking industry; accordingly it is very necessary to investigate the topic of the credit risk management. This paper mainly discusses the importance, current situation, ways and guidelines of the credit risk management for the banking industry. A large number of literatures are integrated in order to illustrate and explain recent developments in both methods and principles of credit risk management. Meanwhile, some evidence is provided. It also investigates and compares the practice of credit risk management in both Chinese and UK banks, and some empirical results are obtained. Finally, some conclusions and suggestions are made for banks to increase their capabilities of credit risk management either for the daily operations or the financial crisis.